2018
DOI: 10.1098/rsif.2018.0681
|View full text |Cite
|
Sign up to set email alerts
|

Pillar versus dimple patterned surfaces for wettability and adhesion with varying scales

Abstract: Inspired by biological topographical surfaces, micropatterned elastomeric surfaces with square pillars and dimples of different geometry scales were fabricated. Their wettability and adhesion properties with various liquids were systematically investigated and compared with flat surfaces. Interesting results were obtained in the case of silicone oil (the toe-pad-like wetting case) in that the scale-dependent wettability and adhesion performed inversely for pillars and dimples. Micropillars significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The interfacial force of friction on soft surfaces can be either reduced or amplified on soft materials, and the behaviors and underlying mechanisms were discussed and analyzed according to the physical fundamentals of wet sliding. In essence, the textures' different abilities to achieve interfacial sliding were attributable to their inverse design orientations to liquids; in this design, the polygonal pillars separated through channels were "open" to liquids, whereas the discrete dimples were "closed" to liquids [126]. It was suggested that the surface-texture-induced decrease in contact area, second lubrication, micro-dynamic pressure, draining effect, and so on imposed significant effects.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The interfacial force of friction on soft surfaces can be either reduced or amplified on soft materials, and the behaviors and underlying mechanisms were discussed and analyzed according to the physical fundamentals of wet sliding. In essence, the textures' different abilities to achieve interfacial sliding were attributable to their inverse design orientations to liquids; in this design, the polygonal pillars separated through channels were "open" to liquids, whereas the discrete dimples were "closed" to liquids [126]. It was suggested that the surface-texture-induced decrease in contact area, second lubrication, micro-dynamic pressure, draining effect, and so on imposed significant effects.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…[19] We are interested in using the landscape and flux analysis to learn the Wu-Xing network model in a global and physical way, e.g., its potential systematic states and how those states could relate to human health or diseases hypothetically. Furthermore, we hope that the quantitative landscape and flux analysis can enlighten us about the pathways leading from a disease state to a healthy state [20][21][22] and shed light on why and how the Wu-Xing theory is so useful beyond its philosophical impact.…”
Section: The Wu-xing Networkmentioning
confidence: 99%
“…In the context of adhesion, micropatterned surfaces commonly adhere better to smooth and even rough substrates as stresses at the contact interface are distributed more homogeneously and cracks are blunted upon detachment of single fibrils. Furthermore, micropatterned surfaces show great potential for improving adhesion under wet conditions and underwater. …”
Section: Introductionmentioning
confidence: 99%